Spinning reserve management in deregulated power markets - Song, Zi Tong (2008)
The broad objective of this research work was to study important aspects of spinning reserve management in the deregulated environment. Studies were carried out based on probabilistic evaluation techniques. One study investigates the spinning reserve requirements in generating systems, in which the transmission system failures are not considered. The other study develops SR allocation methods considering the effects of both generating unit and transmission line failures. These two categories of studies are based on risk evaluation approaches, which are also incorporated with the consideration of cost for reliability, in order to manage the spinning reserve in deregulated power systems.